68Ga-PSMA-PET/CT in Patients With Biochemical Prostate Cancer Recurrence and Negative 18F-Choline-PET/CT. (July 2016) - Bluemel, Christina; Krebs, Markus; Polat, Bülent; Linke, Fränze; Eiber, Matthias; Samnick, Samuel; Lapa, Constantin; Lassmann, Michael; Riedmiller, Hubertus; Czernin, Johannes; Rubello, Domenico; Bley, Thorsten; et al.
Abstract : Purpose: Investigating the value of 68 Ga-PSMA-PET/CT in biochemically recurring prostate cancer patients with negative 18 F-choline-PET/CT. Patients and Methods: One hundred thirty-nine consecutive patients with biochemical recurrence after curative (surgery and/or radiotherapy) therapy were offered participation in this sequential clinical imaging approach. Patients first underwent an 18 F-choline-PET/CT. If negative, an additional 68 Ga-PSMA-PET/CT was offered. One hundred twenty-five of 139 eligible patients were included in the study; 32 patients underwent additional 68 Ga-PSMA-PET/CT. Patients with equivocal findings (n = 5) on 18 F-choline-PET/CT and those who declined the additional 68 Ga-PSMA-PET/CT (n = 9) were excluded. Images were analyzed visually for the presence of suspicious lesions. Findings on PET/CT were correlated with PSA level, PSA doubling time (dt), and PSA velocity (vel). Results: The overall detection rates were 85.6% (107/125) for the sequential imaging approach and 74.4% (93/125) for 18 F-choline-PET/CT alone. 68 Ga-PSMA-PET/CT detected sites of recurrence in 43.8% (14/32) of the choline-negative patients. Detection rates of the sequential imaging approach and 18 F-choline-PET/CT alone increased with higher serum PSA levels and PSA vel. Subgroup analysis of 68 Ga-PSMA-PET/CT in 18 F-choline negative patients revealed detection rates of 28.6%, 45.5%, and 71.4% for PSA levels of 0.2 or greater to less than 1 ng/mL, 1 to 2 ng/mL, and greater than 2 ng/mL, respectively. Conclusions: The sequential imaging approach designed to limit 68 Ga-PSMA imaging to patients with negative choline scans resulted in high detection rates. 68 Ga-PSMA-PET/CT identified sites of recurrent disease in 43.8% of the patients with negative 18 F-choline PET/CT scans.